(untitled) (Archive of Conferences, 2021)
There are several meanings of the word translation. The term "translation" can apply to the general topic field, the product (the text that has been translated), or the process (the act of producing the translation, often known as "translating"). The translator transforms an original written text (the source text or ST) in the original verbal language (the source language or SL) into a written text (the target text or TT) in a different verbal language (the target language or TL) throughout the translation process